2011
DOI: 10.1186/1687-1499-2011-5
|View full text |Cite
|
Sign up to set email alerts
|

State of the art baseband DSP platforms for Software Defined Radio: A survey

Abstract: Software Defined Radio (SDR) is an innovative approach which is becoming a more and more promising technology for future mobile handsets. Several proposals in the field of embedded systems have been introduced by different universities and industries to support SDR applications. This article presents an overview of current platforms and analyzes the related architectural choices, the current issues in SDR, as well as potential future trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A good overview of SDR solutions can be found in Anjum et al [2011]. Recent studies have shown that even multicore architectures can be power efficient in scenarios with tight performance requirements [Horowitz and Dally 2004;Asanovic et al 2006].…”
Section: Introductionmentioning
confidence: 99%
“…A good overview of SDR solutions can be found in Anjum et al [2011]. Recent studies have shown that even multicore architectures can be power efficient in scenarios with tight performance requirements [Horowitz and Dally 2004;Asanovic et al 2006].…”
Section: Introductionmentioning
confidence: 99%
“…In order to find a solution for the optimal coefficient vector of the kth ADIR filter, we substitute Equation (16) back into the cost function in Equation (12) and attain the following quadratic form in w k (n):…”
Section: Optimization Problem Statementmentioning
confidence: 99%
“…The concept of software radio on the other hand relies on the development of DSP technology, that is flexible, reconfigurable, and reprogrammable by software to adapt to an environment where there are multiple services, standards, and frequency bands [11]. Correspondingly, the infrastructure in a software radio system is generally required to use reconfigurable VLSI hardware components such as DSP chip sets [12], FPGAs [13], embedded processors [14], and even general purpose processors [15].…”
Section: Introductionmentioning
confidence: 99%
“…The ADC and DAC are theconnection between the physical world of continuous analog signals and the world of discrete digital samples handled by software.Baseband signal processing operations are defined by programmable designs running on digital hardware.This device is available in various forms on single-chip custom Integrated Circuits (ICs), of which the most commonly used for software radio are Digital Signal Processors (DSPs), Field Programmable Gate Arrays (FPGAs), General-Purpose Processors (GPPs), Application Specific Integrated Circuits (ASICs), and System-on-Chip (SoC) with hardware accelerators [21], [24], [25].…”
Section: Evolve To Build Cognitive Radiomentioning
confidence: 99%